THE EFFECT OF DIFFERENTIATED LEARNING MODEL BASED ON BIOTECHNOLOGY MATERIAL PROJECTS ON SCIENCE LITERACY REVIEW FROM THE LEARNING STYLE OF STUDENTS OF SMAN 1 TURI - Rifqoh, Nidaa; Paidi, Paidi (Jurnal Edukasi Biologi, 2025)
This study aims to examine the effect of a project-based differentiated learning model on the scientific literacy of tenth-grade students in biotechnology material at SMAN 1 Turi, considering students' learning styles. The research method employed was a quasi-experimental design with a non-equivalent control group. The study involved two groups of students: the experimental group, which used the project-based differentiated learning model, and the control group, which used the discovery learning model. The results showed that the average Post-test score of the experimental group increased by 43.2%, from an average Pre-test score of 26.44 to 37.88. In contrast, the control group experienced only a 17% increase, from an average score of 29.91 to 31.41. Additionally, analysis based on learning styles revealed that students with visual learning styles experienced the highest increase in scientific literacy, followed by those with auditory and kinesthetic learning styles. Overall, the application of the project-based differentiated learning model increased learning effectiveness by 76% in the experimental group compared to conventional learning methods. This study concludes that a differentiated, project-based learning model is effective in enhancing students' scientific literacy, particularly in the field of biotechnology. It highlights the importance of considering learning styles in the learning process. These findings offer practical implications for teachers in designing innovative learning experiences tailored to students' individual needs.